Contributions of using GeoGebra software in the study of the derivative (Research, Society and Development, 2020)
This paper presents results of a research that derives from the study of the derivative as a rate of change through the GeoGebra software, conducted with academics from the Federal Institute of Education, Science and Technology of the North of Minas Gerais (IFNMG), Campus Januária. To conduct the research, a short course was offered, held in the mathematics laboratory of the institution, which aimed to verify how digital technologies and GeoGebra software can contribute to the process of teaching and learning the concepts of variation rate and derivative. As a methodology, a qualitative approach was adopted, as it sought to identify the participants' perception and experience during the development of the short course. Thus, it was realized that the use of GeoGebra software as a didactic resource, makes learning and studying the derivative as a rate of variation easier and more viable to understand, and not only through the pencil and paper media in the classroom. teach these contents, thus being able to contribute significantly in the study of the subject and consequently in the Mathematical Education. It was found that the use of GeoGebra software as a didactic resource allows the teaching of the derivative as a rate of variation can facilitate the teaching and learning process.